The Influence of Si and V on the Kinetics of Phase Transformation and Microstructure of Rapidly Solidified Al-Fe-Zr Alloys - Karpe, Blaž (Journal of Mining and Metallurgy, Section B: Metallurgy, 2013)
The influence of Si and V on the precipitation kinetics of the rapidly solidified (RS) Al-Fe-Zr alloys is presented. Precipitation kinetics and microstructural development of RS Al-Fe-Zr alloys with Si or V addition have been investigated by the combination of four point electrical resistance measurement, optical microscopy, transmition electron microscopy (TEM) and scanning electron microscopy (SEM). For verification of the electrical resistivity measurement results differential scanning calorimetry (DSC) and differential thermal analysis (DTA) were also applied. Rapidly solidified samples, in the form of thin ribbons, were prepared with the single roll melt spun technique. For determination of the distinctive temperatures at which microstructural transformations occur in-situ electrical resistivity measurement during heating of the ribbons with various constant heating rates has been used. It was found that microstructure decomposition depends on heating rate and shifts to higher temperatures with increasing heating rate. After heating above the distinctive transition temperatures, heating was stopped and microstructure of the samples examined by electron microscopy.